Artificial intelligence drives success of Khairul Imran Khalip, UMPSA Royal Education Award recipient 2025 - Nur Hartini, Mohd Hatta (UMPSA, 2025)
GAMBANG, 8 November 2025 – Perseverance and deep interest in the field of artificial intelligence (AI) made Khairul Imran Khalip, a Bachelor of Applied Data Analytics with Honours graduate of the Centre for Mathematical Sciences (PSM), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), one of the university’s brightest stars when he was named recipient of the Royal Education Award (Pingat Jaya Cemerlang) 2025.